2020
DOI: 10.1103/physreva.101.043804
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetism, axions, and topology: A first-order operator approach to constitutive responses provides greater freedom

Abstract: We show how the standard constitutive assumptions for the macroscopic Maxwell equations can be relaxed. This is done by arguing that the Maxwellian excitation fields (D, H) should be dispensed with, on the grounds that they (a) cannot be measured, and (b) act solely as gauge potentials for the charge and current. In the resulting theory, it is only the links between the fields (E, B) and the charge and current (ρ, J ) that matter; and so we introduce appropriate linear operator equations that combine the Gauss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 66 publications
(170 reference statements)
0
20
0
Order By: Relevance
“…in ref. [12], this extension permits a new axionic type of interaction with the electromagnetic field. In addition to dispensing with D and H, and in the presence of a spacetime singularity, it has been shown that Maxwell's equations no longer need enforce global charge conservation [11] ; but although posing some intriguing possibilities, this proposal did not include any explicit examples of constitutive relations, material configurations, or field distributions.…”
Section: Topological Axionsmentioning
confidence: 99%
See 4 more Smart Citations
“…in ref. [12], this extension permits a new axionic type of interaction with the electromagnetic field. In addition to dispensing with D and H, and in the presence of a spacetime singularity, it has been shown that Maxwell's equations no longer need enforce global charge conservation [11] ; but although posing some intriguing possibilities, this proposal did not include any explicit examples of constitutive relations, material configurations, or field distributions.…”
Section: Topological Axionsmentioning
confidence: 99%
“…In ref. [12] a minimal extension to Maxwell's equations was considered where D and H did not appear, and which provided an additional axionic term to the vacuum Maxwell's equations. Using this axionic term, we now give in this article an explicit construction of an electromagnetic field configuration which can lead to the breaking of global charge conservation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations